First record of malformed trilobites from the Silurian of Ukraine - Dernov, V.S. (Доповіді НАН України, 2025)
This article presents the first documented case of malformed trilobite exoskeletons from the Silurian of Ukraine. Fossils of animals with injuries and pathologies are of significant palaeobiological value, as they provide essential insights into the evolution of predator-prey interactions, trophic networks, animal behavior, and genetic anomalies. The material under study consists of two pygidia of Bumastus restevensis from the Rykhta Formation (Ludlow, Upper Silurian) in Khmelnytskyi Oblast (western Ukraine, the Volyn-Podillia Monocline). A comparative analysis of these malformed exoskeletons with similar specimens from other global localities reveals that they are unique, with no direct analogues. The injuries observed are interpreted as “predation scars,” indicative of unsuccessful predatory attacks. The distinctive morphology of these malformations suggests that they were most likely inflicted by cephalopods, arthropods, such as phyllocarid crustaceans and/or aquatic chelicerates, or fishes. Досліджено перший задокументований випадок прижиттєво пошкоджених екзоскелетів трилобітів із силурійських відкладів України. Скам’янілості тварин з пошкодженнями та патологіями мають значну палеобіологічну цінність, оскільки дають змогу зрозуміти еволюцію взаємодій хижака і жертви, трофічних мереж, поведінки тварин та генетичних аномалій. Досліджений матеріал складається з двох пігідіїв Bumastus restevensis з рихтівської світи (лудлов, верхній силур) Хмельницької області (Волино-Подільська монокліналь). Порівняльний аналіз цих екзоскелетів з аналогічними зразками з інших місцезнаходжень світу показує, що вони є унікальними і не мають прямих аналогів. Виявлені пошкодження інтерпретуються як «шрами хижацтва», що свідчать про невдалі напади хижаків. Характерна морфологія цих ушкоджень дає підставу припустити, що вони, найімовірніше, були завдані головоногими молюсками, членистоногими, такими як філокариди та/або водні хеліцерові, або рибами.